MPTP- induced Balb/c mice recapitulate compensatory Parkinson’s-like motor features - Mustapha, Musa; Mat Taib, Che Norma; Fakurazi, Sharida; Mohd Moklas, Mohamad Aris (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aimed to assess motor responses and associated pathological changes caused by MPTP neurotoxicity in Balb/c mice. Male mice (13 weeks old, 25-30 g) were divided into four groups and received intraperitoneal injections of normal saline or different doses of MPTP-HCl for five consecutive days. Body weight was monitored, and behavioral tests were conducted. Histological examination with H&E staining was performed on the striatum and substantia nigra. Contrary to expectations, MPTP-treated mice showed increased locomotor activity in the open field test, covering a greater distance and exhibiting more rearing compared to control mice (p<0.05). The catalepsy test also showed lower catalepsy scores in the MPTP-treated group (p<0.05). However, the pole test did not indicate the presence of MPTP-induced bradykinesia (p>0.05). Similarly, the traction and hang tests showed no significant effects of MPTP on motor balance or muscle strength (p>0.05). Among the MPTP-treated groups, the 30 mg/kg MPTP-HCl group displayed the most severe pathological changes, including reactive gliosis, as observed in histological examination. In conclusion, the subacute MPTP mouse model used in this study did not exhibit noticeable motor deficits or significant weight loss in Balb/c mice, possibly due to subthreshold dopamine depletion compensatory mechanisms. This model could provide valuable insights into the compensatory mechanisms involved in Parkinson’s disease. © 2024 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.